Developing a core outcome set for clinical trials of traditional Chinese medicine for rheumatoid arthritis - Yu, Bingbing; Song, Mengge; Yang, Jingdong; Tang, Xiaopo; Xia, Congmin; Zhang, Junjie; Zhao, Xue qi; Jiang, Quan; Han, Man (Frontiers in Medicine, 2025)
ObjectiveWe developed a consensus-based core outcome set (COS) for Traditional Chinese Medicine clinical trials in rheumatoid arthritis (COS-TCM-RA) that to addresses heterogeneity in outcome measurement and reporting across studies.MethodsWe performed a comprehensive systematic review to establish a repository of clinical outcome set for TCM interventions in RA management. Then, a semi-structured interview was conducted to identify additional important outcomes from the patient’s perspective. This was followed by an online three-round Delphi survey conducted with professionals to prioritize and refine clinically relevant outcomes from a previously developed longlist. Core entries were finalized based on three Delphi surveys and one expert consensus meeting.ResultsThe systematic review screened 2,959 records and included 69 eligible studies. From these, a comprehensive list of reported outcomes was extracted and standardized, which after standardization, yielded a final list of 52 unique outcomes for the preliminary consensus process. After semi-structured interviews, three Delphi survey rounds and one consensus meeting, the most important outcomes were determined for COS of Traditional Chinese Medicine for RA (COS-TCM-RA), including physician assessment of global status, Clinical laboratory tests, radiographic assessment, Signs and symptoms, quality of life and security incident.ConclusionThis study developed the first COS-TCM-RA, comprising 11 indicators across five domains: overall disease evaluation, physical and chemical indicators, quality of life, TCM syndromes, and adverse events. By integrating internationally recognized RA assessment tools with patient-reported outcomes and TCM-specific measures, the COS-TCM-RA provides a standardized, multi-dimensional framework to enhance trial quality, improve comparability, and support the integration and internationalization of TCM in evidence-based medicine.